Comparison of Urinary Ace 2 Levels in Individuals with Hypertension and Type 2 Diabetes with Individuals who have Hypertension but not Diabetes - Mah-E-Jabeen Sear, Sara Naeem, Saima Mukhtar, Shaista Hussain, Iram Qamar, Javaria Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In this investigation, the levels of urine Angiotensin Converting Enzyme(ACE2)in patients with Type 2 diabetes and high blood pressure were evaluated and their results compared in individuals having raised blood pressure but they had normal blood sugar control. Given the growing body of evidence linking ACE 2 insufficiency to the etiology of hypertension in diabetic patients, we hoped to find higher Angiotensin Converting Enzyme2 levels in the urine of hypertensive diabetic patients than in those without diabetes. Aim: As a result, new pathways for the development of antihypertensive medicines aimed at protecting Angiotensin Converting Enzyme2, particularly in diabetic patients, may open up. Methods: Two groups, each with 49 subjects, were created from a population of chosen subjects.Patients with diabetes and hypertension were chosen from the Services Institute of Medical Sciences diabetic clinic and medical wards in Lahore. In the clinics, anthropometric characteristics and blood sugar levels were recorded. In the Physiology Laboratory at University of Health Sciences, blood samples were obtained and maintained in order to evaluate biochemical characteristics. Results: We calculated the median value in each group because the data for urine Angiotensin Converting Enzyme 2 readings was not dispersedevenly. Non-diabetic hypertension participants had a median of 26.47mg/dl, while hypertensivediabetic subjects had a median of 22.86mg/dl. This difference in ACE 2 levels in the urine was statistically significant (p0.05). Non-diabetic, hypertension patients had greater urinary Angiotensin Converting Enzyme 2 levels than diabetic, hypertensive patients. Conclusion: Contrary to our expectations, we were unable to confirm that urine Angiotensin Converting Enzyme 2 readingsare higher in people with high arterial pressure and type 2 diabetes mellitus. This is despite the fact that the current study confirmed that both type 2 diabetes mellitus and hypertension are risk factors for chronic kidney disease. Key words: Renin Aldosterone-Angiotensin System, urinary Angiotensin Converting Enzyme 2 levels, Chronic Kidney Disease